Multifocal Capillary Hemangioma-Like Vascular Proliferation of the Kidney Associated With Clear Cell Renal Cell Carcinoma: A Case Report and Review of the Literature. (August 2013) - Fellegara, Giovanni; Rosai, Juan
We report the case of a 69-year-old man who underwent a radical left nephrectomy for a renal mass. Microscopically, the features were those of a clear cell–type renal cell carcinoma associated with 2 foci of capillary hemangioma-like vascular proliferation in the adjacent renal parenchyma. The main differential diagnosis and the possible pathogenesis of this vascular lesion are discussed.